Utility of 18F-FDG-PET/CT in management and prognostication of treatment naïve late-stage soft tissue sarcomas. Issue 7 (18th March 2021) - Singh, Tejesh Pratap; Sharma, Anshul; Sharma, Akshima; Bakhshi, Sameer; Patel, Chetan; Pandey, Anil Kumar; Dhamija, Ekta; Batra, Atul; Kumar, Rakesh
Abstract : Objective: This study evaluated the utility of 18F-fluorodexoyglucose (18F-FDG) positron emission tomography/computed tomography (PET/CT) in staging, grading, and prognostication of Stage III and IV soft tissue sarcomas (STSs). Methods: Forty patients (Median age = 32.5 years; 25 men) with histologically proven STSs, prospectively underwent 18F-FDG-PET/CTs at baseline. Three-dimensional region of interests were drawn encompassing the lesions to calculate standardized uptake values (SUVs) and metabolic tumor volumes (MTVs). After segmentation, Haralick statistical texture analysis was performed. Follow-up was available for 35 patients. Survival at 6 months was 71.4% and at 1 year was 57.1%. Results: American Joint Committee on Cancer Stage III was seen in 23 and Stage IV in 17 patients. None of the baseline quantitative and semi-quantitative parameters could predict response or progression. Only reduction in SUVmax in interim PET/CT correlated with baseline SUVmax (Spearman's Rho = 0.533; P = 0.019). Textural parameters namely 'contrast' in CT ( P = 0.039) and 'difference entropy' in PET/CT ( P = 0.051) could differentiate intermediate from high-grade lesions, with corresponding area under curves being 0.736 (0.533–0.889) and 0.700 (0.518–0.882). M1 disease [Hazard ratio (HR): 3.184 (1.179–8.595); P = 0.022], absence of surgical treatment [HR 0.305 (0.106–0.873), P = 0.027 with surgery], lower MTV/total tumor volume (TTV) [HR: 0.975 (0.953–0.997; P = 0.028] and progressive disease in interim PET/CT [3.483 (0.898–13.515); P = 0.056] were predictors of lower survival in univariate analysis. Only M1 disease was found to be reaching significance in multivariate analysis [HR = 2.683 (0.949–7.580); P = 0.063]. Baseline PET/CT changed management in 12.5% of patients [compared to local-imaging and high-resolution CT chest]; with detection of extra-pulmonary metastases. Though, interim and end of treatment PET/CTs detected more metastatic lesions, management was not impacted. Conclusion: 18F-FDG-PET/CT allows for more accurate M-staging in late-stage STSs, which in turn influences the option of curative surgical resection and thus impacts patient prognosis. Lower baseline MTV/TTV and progression in interim PET/CT are also associated with lower survival. Textural analysis may have a role in noninvasive grading.